Evaluating the teaching ability of double-qualified teachers in Chinese vocational education: A questionnaire validation study - Xu, Shujuan; Ong, Eng Tek (International journal of advanced and applied sciences, 2024)
The Chinese government actively promotes the high-quality development of modern vocational education, placing higher demands on the professionalism and practical skills of "Double-Qualified" Teachers (DQTs) in higher vocational colleges. This initiative encourages teachers to innovate their teaching methods and supports educational reform. As a result, effectively measuring and evaluating the teaching abilities of DQTs in higher vocational colleges has become a significant research focus. This study aims to develop and validate a questionnaire to assess the teaching abilities of DQTs in higher vocational colleges based on the vocational education DQTs' teaching ability evaluation index system and the TPACK framework. The study involved surveying 454 DQTs from eight higher vocational colleges in China using a questionnaire, with data analysis conducted through SPSS 27.0 and Amos 26.0 software. The results indicate that the questionnaire demonstrates high reliability and validity. Among the ten measurement models tested, the six-factor model shows the best fit. This study offers new perspectives and tools for understanding and evaluating the integration of technology into DQTs' subject matter knowledge, with important implications for the training and assessment of DQTs. It also provides insights and recommendations for higher vocational college administrators and DQTs.